Description of two new species, with synonymies and new distribution records, for some species of African Prosopocera Blanchard and Eunidia Erichson (Coleoptera, Cerambycidae, Lamiinae) - (:unkn) unknown (My University, 2023)
New information on several African Lamiinae is provided. The following synonyms are proposed: Prosopocera (Alphitopola) albosignata Breuning, 1938 and P. (A.) bicornuta Breuning, 1971 are synonymized with P. (A.) paykullii (Fåhraeus, 1872); P. (Dalterus) matillai Báguena, 1952 is synonymized with P. (A.) gahani (Aurivillius, 1925); P. (D.) holoflava Breuning, 1981 is synonymized with P. (A.) infragrisea Breuning, 1950; Eunidia diversipes Breuning, 1961 is synonymized with E. timida Pascoe, 1864; E. jeanneli Breuning, 1939 is synonymized with E. pygmaea Fåhraeus, 1872; E. vagefasciata Breuning, 1955 is synonymized with E. subfasciata Gahan 1898; E. flavoornata Breuning, 1981 is synonymized with E. thomseni Distant, 1898; E. obliquealbovittata Hunt & Breuning, 1957 is synonymized with E. fasciata Gahan, 1904; E. mediomaculatoides Breuning, 1981 is synonymized with E. bifasciata Aurivillius, 1911; E. subnebulosa Breuning, 1961 is synonymized with E. flavomarmorata Breuning, 1939; E. olivacea Breuning, 1954 is synonymized with E. albopicta Breuning, 1939; E. politzari Siess, 1981 is synonymized with E. similis Breuning, 1942; E. deceptrix camerunica Teocchi, 1994 and E. deceptrix gabonicola Teocchi, Jiroux & Sudre, 2004 are synonymized with E. lujai Breuning 1951. Two new species are described from South Africa: P. (D.) ndumoensis sp. nov. and E. albomaculata sp. nov.
Keywords: African Research